Handbook of manufacturing engineering and technology - Nee, A. Y. C. 1948- (Andrew Yeh Chris).; SpringerLink (Online service). (London Springer London, 2015)
The Springer Reference Work Handbook of Manufacturing Engineering and Technology provides overviews and in-depth and authoritative analyses on the basic and cutting-edge manufacturing technologies and sciences across a broad spectrum of areas. These topics are commonly encountered in industries as well as in academia. Manufacturing engineering curricula across universities are now essential topics covered in major universities worldwide.
Electronic reproduction.
Keywords: Production engineering -- Handbooks, manuals, etc; Electronic books